Korean Red Ginseng increases defective pol gene in peripheral blood mononuclear cells of HIV-1–infected patients; inhibition of its detection during ginseng-based combination therapy - Young Keol Cho (Journal of Ginseng Research, 2019)
Background: We have reported that defective nef and gag genes are induced in HIV-1–infected patients treated with Korean Red Ginseng (KRG). Methods: To investigate whether KRG treatment and highly active antiretroviral therapy (HAART) affect genetic defects in the pol gene, we amplified and sequenced a partial pol gene (p-pol) containing the integrase portion (1.2 kb) by nested PCR with sequential peripheral blood mononuclear cells over 20 years and compared it with those patients at baseline, in control patients, those taking ginseng-based combination therapy (GCT; KRG plus combinational antiretroviral therapy) and HAART alone. We also compared our findings to look for the full-length pol gene (pol) (3.0-kb) Results: Twenty-patients infected with subtype B were treated with KRG for 116 ± 58 months in the absence of HAART. Internal deletion in the pol gene (Δpol) was significantly higher in the KRG group (11.9%) than in the control group and at baseline; its detection was significantly inhibited during GCT as much as during HAART. In addition, the Δpol in p-pol significantly depended on the duration of KRG treatment. In pol, the proportion of Δpol was significantly higher in the KRG group (38.7%) than in the control group, and it was significantly inhibited during GCT and HAART. In contrast, the proportion of stop codon appeared not to be affected by KRG treatment. The PCR success rate was significantly decreased with longer GCT. Conclusion: The proportion of Δpol depends on template size as well as KRG treatment. HAART decreases the detection of Δpol. Keywords: AIDS, HIV-1, Korean Red Ginseng, Internal deletion, pol